Correlation of interleukin-18 gene polymorphism with the susceptibility of condyloma acuminatum in Chinese population - Wang,Changyuan (2019)
ABSTRACT Host immunogenetic setting is involved in the regulation of human papillomavirus (HPV) infection and development of condyloma acuminatum (CA). We investigated the correlation of two common single nucleotide polymorphisms (SNPs) (−607C/A and −137G/C) of IL-18 with the susceptibility of CA in a large Chinese cohort. Out of 408 CA patients analyzed, 300 had HPV infection transmitted through sexual contact (SC) and 108 through non-sexual contact (NSC). In addition, 360 healthy volunteers were enrolled as controls. SNPs at positions −607C/A and −137G/C in IL-18 promoter were analyzed. Comparing CA patients to healthy controls, no dominant relevance was found between the IL-18 promoter −607 C/A or −137G/C polymorphisms and the CA disease either identified genotypically (p > 0.05) or by allelically (p > 0.05). However, the IL-18 promoter −137G/C polymorphism genotype and allele frequencies in the NSC CA group, but not between in the SC group, were significantly higher than in the controls. There was no dominant relevance between IL-18-607C/A polymorphism genotype and allele frequencies among SC, NSC CA patients, and controls. Our study demonstrates that polymorphism −137G/C in IL-18 promoter is significantly correlated with risk of CA in NSC patients.